An Industry Survey of the Composition and Variability of Soybean Gums and Soapstocks Across US Soybean Processing Plants - Katelyn N. Gaffield; Robert D. Goodband; Joel M. DeRouchey; Mike D. Tokach; Jason C. Woodworth; Gordon Denny; Paul Smolen; Carmen Slipher; Hari B. Krishnan; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2024)
Depending on the soybean processing plant, gums and soapstocks may be added back to soybean meal during soybean processing. Despite the potential effects on soybean meal quality, there is limited information on the composition and variation in soybean by-products and the resulting soybean meal if by-products are added back during processing. A total of 36 soybean by-product samples from 14 plants across eight different companies were used in an industry survey evaluating the composition and variation of soybean gums and soapstocks across the US. All soybean processing plants within the study produced at least one of the two by-products: soybean gums or soybean soapstocks. Soybean by-product and soybean meal samples were collected at two different timepoints: May to July 2023 and October to November 2023. The individual plants surveyed constitute approximately 30% of total US soybean meal production, with the eight participating companies representing 80% of the total US soybean meal production. By-products were analyzed for lipid quality criteria including moisture, fat by acid hydrolysis, fatty acid analysis, and oxidation markers. Furthermore, soybean meal samples were submitted for analysis of proximate composition, neutral detergent fiber, Ca, P, and trypsin inhibitor activity. Soybean gums had a greater (P ≤ 0.05) percentage of acid hydrolyzed fat and p-Anisidine value compared to soybean soapstocks. Soybean soapstocks tended to have a greater (P = 0.085) percentage of moisture and volatile matter, as well as an increased (P = 0.052) concentration of insoluble impurities compared with soybean gums. Most notably, there was considerable variation in the composition of by-product samples between processing plants indicating differences in processing procedures or incoming soybean quality. Soybean meal containing added soybean by-products had 61% greater (P < 0.05) ether extract than soybean meal samples not containing added soybean by-products on a dry matter basis, but there was no difference (P < 0.10) in crude protein. Furthermore, trypsin inhibitor activity varied considerably between plants with values ranging from 1.45 to 9.26 TIU/mg of seed powder, regardless of by-product inclusion. These results provide information on the composition and variation in soybean by-products across various processing plants; however, further information is still needed to evaluate their subsequent effects on livestock diets.
Keywords: gums; lipid quality; soapstocks; soybean meal quality; soybean by-products; trypsin inhibitor activity